2020
DOI: 10.1002/for.2698
|View full text |Cite
|
Sign up to set email alerts
|

Neural network structure identification in inflation forecasting

Abstract: Neural networks (NNs) are appropriate to use in time series analysis under conditions of unfulfilled assumptions, i.e., non-normality and nonlinearity. The aim of this paper is to propose means of addressing identified shortcomings with the objective of identifying the NN structure for inflation forecasting. The research is based on a theoretical model that includes the characteristics of demand-pull and cost-push inflation; i.e., it uses the labor market, financial and external factors, and lagged inflation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Most previous studies have focused on inflation forecasting using ARIMA, STAR and VAR models, see, e.g., [7,[12][13][14]. Some of the studies have compared traditional econometric models against neural networks when forecasting inflation, see, e.g., [15][16][17][18], but only a few of them have dealt with the recurrent neural network as the competing one among other neural network structures, see, e.g., [10,19,20].…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies have focused on inflation forecasting using ARIMA, STAR and VAR models, see, e.g., [7,[12][13][14]. Some of the studies have compared traditional econometric models against neural networks when forecasting inflation, see, e.g., [15][16][17][18], but only a few of them have dealt with the recurrent neural network as the competing one among other neural network structures, see, e.g., [10,19,20].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Ref. [10] showed that JNN has a significantly better forecasting performance one and six months ahead compared to the FNN. On the other hand, [18] compared machine learning models, including FNNs, with standard time-series models and concluded that multivariate models produce the most precise results in all horizons and that there is no single best model to forecast inflation.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Atsalakis [30] focuses specifically on the area of emission allowance prices, creating a model based on computational intelligence techniques for their prediction, including a hybrid neurofusion controller which forms a closed-loop feedback mechanism; an artificial neural network system (ANN) and an adaptive inference system (ANFIS). In their work, Šestanović and Arenrić [31] look for the optimal neural network for inflation prediction.…”
Section: Company Specific Modelmentioning
confidence: 99%
“…Conversely, Estiko and Wahyuddin (2019) found that ANN outperformed ARIMA when forecasting inflation in Indonesia. Finally, in a recent study forecasting inflation of the Euro, Sestanović and Arnerić (2021) found that the Jordan NN, outperformed a feedforward NN.…”
Section: Introductionmentioning
confidence: 96%